A new data hiding algorithm based on direction vector for digital images - Tuncer, Turker; Avci, Engin (Institute of Electrical and Electronics Engineers Inc., 2015)
Nowadays, data hiding algorithms are widely used. These algorithms performance criteria of reliability, capacity, transparency and robustness. Reliability of data hiding algorithms in use today has become the subject of debate. In this study, the vector direction based on a high capacity data hiding algorithm is proposed. This process image data hiding algorithm that case gezilerek 3X3 blocks are performed. Each 3×3 block of 4 bits are embedded. To reduce the variation in carrier has benefited the edge extraction algorithms. The algorithm used is reliable, less the change in carrier and a high-capacity data hiding algorithm. © 2015 IEEE.
Sayisal Görüntüler için Yön Vektörü Tabanli Yeni Bir Veri Gizleme Algoritmasi
2015 23rd Signal Processing and Communications Applications Conference, SIU 2015 -- 16 May 2015 through 19 May 2015 -- Malatya -- 113052
Keywords: Data hiding; Edge detector; Image processing; Steganography